Biomasa y carbono en plantaciones de Terminalia amazonia en la zona Sur de Costa Rica - Montero, M.; Kanninen, M. (2003)
Biomass and carbon in Terminalia amazonia plantations in the South of Costa Rica. The study was carried out in a spacing trial with an experimental design consisting of randomized complete blocks, with three treatments and three replicates. Treatments were 2 m x 2 m (2500 trees/ha), 2.5 m x 2.5 m (1.600 trees/ha) and 3 m x 3 m (1111 trees/ha). The trial is located in Mogos, Osa Peninsula, Puntarenas, Costa Rica. Results at 10 years of age indicate significant differences between treatments. These differences suggest that the stand density of 1600 trees/ha is the best option to maximize diameter growth and total height, as well as a greater yield of Terminalia amazonia. Results of wood density found in this study are similar to those reported in the literature (0.70 g/cm3). The biomass expansion factor (BEF) for this plantation is similar to that reported for natural forests. The factor to calculate the BEF for an individual tree is 1.3, and 1.2 per hectare. The allometric models adjusted for predicting biomass on the different tree components in relation to dbh had a satisfactory adjustment. The determination coefficients explained an average of 93% of data variability. The carbon fraction determined for the tree components of T. amazonia, as well as the different spacings, did not show a significant variation. The average values for stem, branches and foliage were 0.48, 0.43, and 0.42, respectively. The aboveground biomass per tree component under the 3 m x 3 m spacing differed from the other two treatments. Dry biomass production was greater at 1600 trees/ha density. The carbon stored by different tree components at the age of 10 years suggests that T. amazonia stores carbon in a more efficient manner under the 2.5 m x 2.5 m spacing (1600 trees/ha), with a rate of 4.9 Mg/ha/year.